Chemopreventive effect of a novel, selective TACE inhibitor on DMBA- and TPA-induced skin carcinogenesis. (August 2014) - Sharma, Manoranjan; Mohapatra, Jogeswar; Argade, Anil; Deshpande, Shrikalp S.; Shah, Gaurang B.; Chatterjee, Abhijit; Jain, Mukul R.
Abstract Context: Tumor necrosis factor (TNF)-α, a potent proinflammatory cytokine, plays a major role in the pathogenesis of cancer. TNF-α converting enzyme (TACE) mediates processing and release of biologically active TNF-α. Objective: We aimed to investigate the effect of a novel, selective TACE inhibitor (compound 11p) on skin inflammation and associated tumorigenesis in mice. Methods: Skin edema was induced in mice by dermal application 12-O-tetradecanoylphorbol-13-acetate (TPA) solution in acetone on to the ear and the effect of post-treatment of compound 11p (topical application) was evaluated. Edema and inflammation was assessed by measuring ear thickness, weight of skin punch and cytokine levels. Skin cancer in mice was initiated by single topical application of 7, 12-dimethylbenz[a]anthracene (DMBA) and promoted by repeated TPA application for 20 weeks. The effect of compound 11p on papilloma incidence and multiplicity was evaluated. Results: Treatment with compound 11p strongly suppressed TPA-induced elevation in skin thickness and weight. A dose-dependent suppression in TPA-mediated TNF-α, IL-6, IFN-γ, IL-17 and PGE2 levels which was associated with a decrease in infiltration of inflammatory cells was also observed with the treatment. Moreover, compound 11p treatment delayed the onset, markedly reduced the papilloma incidence and multiplicity persuaded by DMBA and TPA. Discussion and conclusion: These findings suggest that selective blockade of TACE suppresses TPA-induced epidermal hyperplasia, inflammatory cell infiltration and cytokine level. Inhibition of inflammatory events related to tumor growth might have led to the anti-tumor effect in mouse skin cancer model induced by DMBA and TPA.